The Influence of Ethical Climate, Organizational Commitment and Psychological Safety on Ethical Work Behavior in Public Service Agencies - Djunaedi Djunaedi; Pande Gde Bagus Naya Primananda; Iwan Henri Kusnadi; Riesna Apramilda (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The current research attempts to investigate the aforementioned factors along with several others as they apply to public service institutions: the ethical climate, organizational commitment, and psychological safety. The premise of the study is that these three factors are instrumental in building a transparent, accountable, and public-oriented government service culture. The researchers selected a quantitative explanatory design in which they surveyed 200 civil servants via purposive sampling to collect their data. The data analysis involved confirming the validation, reliability, and classical assumptions first and then applying multiple linear regression analysis to obtain results. The outcome discloses that ethical climate, organizational commitment, and psychological safety significantly and positively influence ethical work behavior. The research contributes on the theoretical level to the literature with regard to the public sector and organizational behavior by providing empirical evidence of the factors influencing the ethical conduct of civil servants. From a practical point of view, the study's outcomes suggest that the integrity, commitment, and psychological safety of the public service agencies' policy and management practices would positively affect the quality of service provided to the public.